GENTRIFICACIÓN EN CENTROS HISTÓRICOS: UNA DISCUSIÓN CONCEPTUAL - Roldán Villanueva, Omar Alexis (2017)
The article presented here seeks to understand gentrification in Latin America through a con- ceptual analysis. It proposes that gentrification cannot be understood only as an isolated issue, but rather that it is connected to urban heritage management –as a common effect of urban planning– and to the historic center –as an area of the city which is not only specific in a historical sense, but also in terms of the historicity of the city–. Gentrification tends to develop in central spaces in other latitudes; the desire to understand the possibilities of Latin American historical centers as spaces that generate gentrification, or not, emerges from such a phenomenon. In addi- tion to a search to deepen concepts and theories, the purpose of the paper is to determine, on the basis of Latin American cases, if it is objective to speak of gentrification in the historical centers of Latin America and what particularities the region may have regarding such processes. Gentrifi- cation is currently a controversial category due to its Anglo-Saxon origin and any Euro-American conceptualization is put into question by many Latin American authors, in terms of the appropri- ateness of the use of concept.